Geology of the capote granite, southern segment of trÊs cÓrregos batholith, South of São Paulo state - Vieira, Otávio Augusto Ruiz Paccola [UNESP]; Godoy, Antonio Misson [UNESP]; Luvizotto, George Luiz [UNESP] (UNESP - Universidade Estadual Paulista, 2021)
The Capote Granite constitutes an elongated intrusive body of 600 km2, located near the Capão Bonito, Guapiara and Ribeirão Branco and in the extreme northeast of Araçaíba region. It is associated with the Mantiqueira Central Province and correlated with the Apiaí Terra neoproterozoic evolution. The batholith rocks were divided into four facies: Paiol da Telha, Serra Velha, Capote Association and Apiaí-Mirim. Petrographically, these rocks constitute hornblende-biotite granodiorite to quartz monzonite (Paiol da Telha and Serra Velha facies), biotite monzogranite to syenogranite with hornblende (Capote Association and Apiaí Mirim facies), leukocratic, predominantly inequigranular, porphyritic, white to pink microcline phenocrystals with dimensions of less than 3 to 4 cm, fine to medium granulation, gray or pink and isotropic to sub-oriented with slight milonitic and/or cataclastic foliation. The Apiaí-Mirim facies is considered one indiscriminated facies, due to the high deformation rate, which generates milonites and cataclasites. Analyzes of mineral chemistry determine as main mineralogy microcline, oligoclase, amphibole (edenite to ferroedenite) and biotite (phlogopite and annita), with ferroedenite and annita more common in the most evolved facies. These granitoid rocks have a calc-alkaline character, peraluminous, I cordilleran type, sin collisional of a magmatic arc environment and generated by the fusion of rocks from the lower crust.
Geologia do granito capote, segmento meridional do batolito três corregos, sul do estado de São Paulo
Keywords: Capote Granite; Geochemistry; Petrography